2010
DOI: 10.5424/sjar/2010081-1149
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synergistic antibacterial activity of Melissa officinalis L. and some preservatives

Abstract: The aim of this study was to investigate the antibacterial activity of aqueous, ethanol and ethyl acetate extracts of the species Melissa officinalis L. and their in vitro synergistic action with preservatives, namely: sodium nitrite, sodium benzoate and potassium sorbate against selected food spoiling bacteria, for a potential use in food industry. Synergistic action was noticed in almost every combination between plant extracts and preservatives. This work showed that the active compounds from ethanol, ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…A total of four bacterial strains that grow primarily on skin and constitute part of the intestinal flora and food contaminants ( 4 ) were used to determine the antibacterial effect of medicinal plant extracts. The following bacterial strains were used: Escherichia coli (cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of four bacterial strains that grow primarily on skin and constitute part of the intestinal flora and food contaminants ( 4 ) were used to determine the antibacterial effect of medicinal plant extracts. The following bacterial strains were used: Escherichia coli (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Its members also strengthen and stimulate, and have specific effects associated with a particular organ or system. It has been demonstrated that the active compounds present in plants from the Lamiaceae family have natural antibacterial ( 4 , 5 ), antioxidant ( 6 , 7 ), antifungal ( 8 ) and antitumor effects ( 9 , 10 ) which suggests that they may be viable alternatives to synthetic products in the therapy of various diseases. Thus, the proven benefits on human health represent the main reason why various medicinal plant species belonging to the Lamiaceae family are increasingly exploited nowadays, in various formulations.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity of lemon balm has been evaluated by many authors [17][18][19]. In the food industry, lemon balm and its extracts are used as spices, natural antioxidants, and stabilizers [20,21].…”
mentioning
confidence: 99%
“…The use of lemon balm in folk medicine and its multiple perceived health benefits have led to intense research activity in the fields of phytotherapy and pharmacognosy. Several studies have been conducted to evaluate the chemical composition of lemon balm (Pereira et al 2014), its anxiolytic activity (Vafaei et al 2005;Taiwo et al 2012), and nutraceutical and antioxidant properties (Dias et al 2012;Luño et al 2015) as well as its potential as an antimicrobial (Stanojevic et al 2010;Rabbani et al 2016), a neuroprotective (L opez et al 2009;Kamdem et al 2013), or a carcinopreventive (Sousa et al 2004;Weidner et al 2015) agent.…”
Section: Introductionmentioning
confidence: 99%